Webrooming in a Role of Motivating Online Shopping in Some Indonesian Marketplace Choice - WB, Sylvia Kartika; Widiastuti, Fitri; Syafri, Rista Aldilla (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
The rapidly changing retail landscape and associated changes in consumer preferences have forcing retailers to adopt multi-channel strategies rather than just using one chancellor's solution (Verhoef et al.,2015) As a result, customers engage in shopping behavior cross channels, such as showrooming and webrooming more than ever. Consumer Survey the Annual Global Retail conducted by PwC Indonesia in 2015 revealed that 70% of global consumers collect information online to make purchases offline. Webroomers have a greater perception of saving time, effort for make the right purchases, as well as smart shopping better than showroomers. Unfortunately, most research so far has focused on showrooming spaces (Eriksson & Fagerstrøm, 2019) and there is still very little research using webrooming spaces at the individual level, although this topic is constantly being called for action. Although these variables are valid and enriching, they do not explain everything observed variations in online space usage behavior and more research is needed carry on. The aim of this research is how far the webrooming component affects motivation interest in online shopping in several marketplace choices in Indonesia and how to implement it Webrooming can help marketplaces in Indonesia influence Indonesian people's online shopping motivation. Researchers employ an exploratory research approach, which seeks to gather information, data, and facts on a particular topic or issue. This is done using quantitative methods, with the data being analyzed statistically through the Structural Equation Modeling (SEM) technique, specifically utilizing Partial Least Squares (PLS). The primary data for this study is collected via questionnaires, which are distributed both through Google Forms and in person. The sampling method used is convenience sampling, where individuals encountered by the researcher who are deemed appropriate as data sources and are willing to participate are selected as samples. The sample in this research was marketplace users who had previously done webrooming, so the sample obtained was 188 people. The research findings showed that the motivation variable or shopping intention, the marketplace channel showed significant results on webrooming behavior. The research results show that many consumers use the marketplace to compare prices before deciding to buy a product offline. Research indicates that easily accessible price comparisons on platforms such as Tokopedia and Shopee encourage users to be more careful in making decisions. Access to complete product information and reviews from other users on the marketplace greatly influences consumer decisions. The research also shows differences in marketplace preferences, with some consumers preferring platforms that offer flexible return policies and responsive customer service.